Solve using the quadratic formula


This lesson shows how to solve using the quadratic formula. To use the quadratic formula, you need to identify a, b, and c in the standard of a quadratic equation


Quadratic Formula is x = (-b ± √(b2 - 4ac))/2a


The standard form is ax2 + bx + c = 0

1) for 6x2 + 8x + 7 = 0 we get a = 6, b = 8, and c = 7

2) for x2 + 8x - 7 = 0 we get a = 1, b = 8, and c = -7

2) for -x2 - 8x + 7 = 0 we get a = -1, b = -8, and c = 7


Example #1:


Solve using the quadratic formula x2 + 8x + 7 = 0

a = 1, b = 8, and c = 7

x = (-b ± √(b2 - 4ac)) / 2a

x = (-8 ± √(82 - 4 × 1 × 7)) / 2 × 1

x = (-8 ± √(64 - 4 × 1 × 7)) / 2

x = (-8 ± √(64 - 4 × 7)) / 2

x = (-8 ± √(64 - 28)) / 2

x = (-8 ± √(36)) / 2

x = (-8 ± 6 ) / 2

x1 = (-8 + 6 ) / 2

x1 = (-2 ) / 2

x1 = -1

x2 = (-8 - 6 ) / 2

x2 = (-14 ) / 2

x2 = -7


Example #2:


Solve using the quadratic formula 4x2 - 11x - 3 = 0

a = 4, b = -11, and c = -3

x = (-b ± √(b2 - 4ac)) / 2a

x = (- -11 ± √(  (-11)2  - 4 × 4 × -3)) / 2 × 4

x = (11 ± √(121 - 4 × 4 × -3)) / 8

x = (11 ± √(121 - 4 × -12)) / 8

x = (11 ± √(121 + 48)) / 8

x = (11 ± √(169)) / 8

x = (11 ± 13 ) / 8

x1 = (11 + 13 ) / 8

x1 = (24 ) / 8

x1 = 3

x2 = (11 - 13 ) / 8

x2 = (-2 ) / 8

x2 = -1/4




Example #3:


Solve using the quadratic formula x2 + x - 2 = 0

a = 1, b = 1, and c = -2

x = (-b ± √(b2 - 4ac)) / 2a

x = (- 1 ± √(  (1)2  - 4 × 1 × -2)) / 2 × 1

x = (-1 ± √(1 - 4 × 1 × -2)) / 2

x = (-1 ± √(1 - 4 × -2)) / 2

x = (-1 ± √(1 + 8)) / 2

x = (-1 ± √(9)) / 2

x = (-1 ± 3 ) / 2

x1 = (-1 + 3 ) / 2

x1 = (2) / 2

x1 = 1

x2 = (-1 - 3 ) / 2

x2 = (-4 ) / 2

x2 = -2







Recent Articles

  1. 100 Hard Word Problems in Algebra

    Sep 11, 17 05:06 PM

    Easy to follow solution to 100 hard word problems in algebra

    Read More

New math lessons

Your email is safe with us. We will only use it to inform you about new math lessons.

            Follow me on Pinterest


Page copy protected against web site content infringement by Copyscape